ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN SHARIAH GOVERNANCE PADA BANK UMUM SYARIAH ANALISIS PADA LAPORAN TAHUNAN PERIODE 2013-2017 - Mukhibbatul Adawiyah; Noven Suprayogi (Universitas Airlangga, 2019)
This study aims to find out the simultaneous and partial influence of Firm Age, Firm Size, Third-Party Funds Growth And Predicate of GCG Self Assesment On The Level of Shariah Governance Disclosure. This study use quantitative approach. The analysis technique used is the panel data regression. The sampling technique is purposive sampling and obtain a sample of 11 shariah commercial banks in Indonesia. This result of this study indicated that firm age, firm size, and thirs-party funds growth variables partially have a positive and significant effect, while predicate of GCG self assesment have not significant effect. Nonetheless simultaneously Firm Age, Firm Size, third-party funds growth and predicate of GCG self assesment have a significant effect on the level of shariah governance disclosure on shariah commercial banks in Indonesia.Keywords: Firm Age, Firm Size, third-party funds growth, predicate of GCG self assesment, level of shariah governance disclosure, shariah commercial banks